Influence of site conditions and silvicultural practice on the wood density of Scots pine (Pinus sylvestris L.) - a case study from the Doksy locality, Czech Republic - Ondřej SCHÖNFELDER; Aleš ZEIDLER; Vlastimil BORŮVKA; Lukáš BÍLEK (Journal of Forest Science, 2017)
After spruce, the Scots pine (Pinus sylvestris Linnaeus) is the second most important commercial coniferous tree species in the Czech Republic. However, we are finding out that awareness of the variability of properties, and possibilities to affect them, are noticeably small for this type of tree species in our conditions. The goal of this study is to primarily evaluate the importance of site conditions, silvicultural measures and other factors for the density of Scots pine wood in the Doksy locality in the Czech Republic. The Doksy locality is represented by three forest stands with different silvicultural history. Samples were taken from each stand, the basal and central parts of which were subsequently processed for test samples with dimensions of 20 × 20 × 30 mm. Wood density at 12% moisture content was ascertained in the test samples. The highest density value of 0.541 g.cm-3 was reached in a stand that is regenerated using the shelterwood method with long regeneration period, and the lowest density value of 0.488 g.cm-3 was recorded in a stand that was regenerated using the clear-cutting method. From a forestry perspective, it can be further stated that the wood density of Scots pine is also affected by the site conditions and position of samples in the trunk.